Misdivision analysis of centromere structure in maize. - Kaszás, E (1996)
The size and organization of a representative plant centromere from the supernumerary B chromosome were determined using a repeated sequence specific to the centric region. Several derivatives of the B chromosome that suffered from misdivision of the centromere were analyzed for the content and organization of their B repeat. In all these derivatives, major rearrangements were detected. Some misdivisions produced a significant reduction in size of the B-specific cluster. These results demonstrate that the B repeat is part of the functional centromere, that it is spread throughout its length, and that plant centromeres are composed of repeat units that can be significantly changed in copy number without a change in function.